2002
DOI: 10.1016/s0006-3495(02)75399-x
|View full text |Cite
|
Sign up to set email alerts
|

Salt-Induced Conformation and Interaction Changes of Nucleosome Core Particles

Abstract: Small angle x-ray scattering was used to follow changes in the conformation and interactions of nucleosome core particles (NCP) as a function of the monovalent salt concentration C(s). The maximal extension (D(max)) of the NCP (145 +/- 3-bp DNA) increases from 137 +/- 5 A to 165 +/- 5 A when C(s) rises from 10 to 50 mM and remains constant with further increases of C(s) up to 200 mM. In view of the very weak increase of the R(g) value in the same C(s) range, we attribute this D(max) variation to tail extension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
126
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(165 citation statements)
references
References 45 publications
37
126
1
1
Order By: Relevance
“…In fact, we have tested different orientations of histone tails in our DiSCO model and found that the exact positions of the tails do not matter. The array stays in moderate folded forms at high salt as long as the tails protrude from nucleosome cores; the tails prefer protrusion at high salt as observed in experiments (62). Another approximation in the present model is our use of Debye-Hückel approximation, which accounts for neither the nonlinear effect from the polyelectrolyte feature of both the linker DNA and the nucleosomal DNA nor the contribution of desolvation terms.…”
Section: Discussionmentioning
confidence: 87%
“…In fact, we have tested different orientations of histone tails in our DiSCO model and found that the exact positions of the tails do not matter. The array stays in moderate folded forms at high salt as long as the tails protrude from nucleosome cores; the tails prefer protrusion at high salt as observed in experiments (62). Another approximation in the present model is our use of Debye-Hückel approximation, which accounts for neither the nonlinear effect from the polyelectrolyte feature of both the linker DNA and the nucleosomal DNA nor the contribution of desolvation terms.…”
Section: Discussionmentioning
confidence: 87%
“…6,7,16,20 Although the distribution of DNA chain segments in DNA brushes has not been fully resolved, 16,17 we here use the Alexander approximation, which assumes that the local concentration of Kuhn segments is uniform in the brush region. 21 This treatment highlights the roles played by transcription for chromatin structures, rather than the details of brush models.…”
Section: Modelmentioning
confidence: 99%
“…For instance, close 345 The presence of 8 highly basic Arg/Lys-rich flexible N-terminal histone tails was associated with the NCP aggregation via ''tail-bridging'' effect in some experiments, 346 computer simulations, [347][348][349] and theoretical models. 310,350 Tails-mediated NCP-NCP attraction, 351 present at elevated [salt] only, seems however to be not very specific with respect to mutual NCP-NCP orientations and as such is not likely to generate highlystructured chromatin fibers. Conversely, the close-range DNA-mediated ES side-to-side NCP-NCP contacts might be capable of doing so.…”
Section: B Dense Phases Of Ncpsmentioning
confidence: 99%